Depth Dependent Focal Mechanisms of Volcanic Deep Low‐Frequency Earthquakes in Northeast Japan. Issue 12 (12th December 2021) - Oikawa, Genki; Aso, Naofumi; Nakajima, Junichi
Abstract: Deep low‐frequency earthquakes (LFEs) in Northeast Japan occur beneath active volcanoes at depths of 10–40 km. These volcanic LFEs radiate low‐frequency seismic waves, with most energy at 2–8 Hz, despite their low magnitudes (M < 2). Although many previous studies have obtained various focal mechanisms with non‐double‐couple components and suggested physical processes related to magma, the universal physical process is poorly understood. Therefore, we comprehensively determined the focal mechanisms of 264 LFEs for 26 volcanic regions in Northeast Japan using S/P amplitude ratios. Many of the obtained solutions have large double‐couple components with small compensated linear vector dipole components. Such source mechanisms can be explained by shear slip on the bending fault. We observed that the plunge of the null axis is as small as 20–30º at depths of 15–25 km, whereas it becomes larger and more varied at depths of 25–35 km. We interpreted that the regional stress field is relatively homogeneous in the middle of the crust, whereas it may be altered near the Moho discontinuity due to thermal stress or other effects related to potential magmatic processes. In addition, after quantitatively investigating the possible triggering of LFEs due to static stress changes in both the 2008 Iwate‐Miyagi earthquake and the 2011 Tohoku earthquake, we concluded that LFEs might have been triggered by substantial stress changes caused by large earthquakes in some regions. Plain Language Summary: Deep slow earthquakes occurring near active volcanoes are thought to be related to deep magmatism. However, their physical processes are not well understood because of the lack of observations. In this study, to reveal their universal processes, we determined the focal mechanisms of 264 events in 26 volcanic regions in Northeast Japan, where deep slow earthquakes occur actively, and high‐quality waveform data are available. Many of the obtained 264 focal mechanisms are dominated by shear slip components, similar to ordinary earthquakes. We found that the focal mechanisms of shallower events (<25 km) are consistent with the regional stress field in Northeast Japan, while those of deeper events (>25 km) vary. Such disturbances in the stress field at greater depths may be generated by stagnated magma near the Moho discontinuity. We also found that the activity of deep slow earthquakes is triggered by stress changes induced by large earthquakes. Key Points: Many of the 264 focal mechanisms of deep low‐frequency earthquakes in 26 regions have large double‐couple components The plunge of the null axis is as small as 20–30º at 15–25 km, but it becomes larger and more diverse at 25–35 km The triggering potential of large earthquakes correlates with the activity changes of deep low‐frequency earthquakes